Internalization of Sufism-Based Character Education Through Musicalization of Qasida Burdah - Ainusyamsi, Fadlil Yani (Jurnal Penelitian Pendidikan Islam, 2020)
This study aims to internalize Sufism-based character education through the musicalization of Qasida Burdah. This research uses a social action method, self-reflection research conducted by researchers together with participants in social situations to improve, solve problems, empower, develop, or advocate for certain social communities. This research was conducted at Darussalam Islamic Boarding School in Ciamis-Indonesia for five months, starting from October 2019 to February 2020. The internalization of Sufism-based character education through Qasida Burdah was carried out through three stages of action. The first stage is 'deepening words' as a basic understanding to animate every poem text Qasida Burdah. The second stage is the 'deepening of meaning' as a step to instill substantial value from the poetry of Qasida Burdah. The final stage is to appreciate music as a preliminary reflection-praxis to the depth of the word and meaning of the poetry of Qasida Burdah. Through Qasida Burdah's musicalization, students (santri) become more religious, more disciplined, more respectful of others, more respectful of differences, more tolerant, not rude, arrogant, pretentious, and ignorant of others. This shows that Sufism-based character development can be done using a variety of media, including musical media.